2011
DOI: 10.1111/j.1460-9568.2010.07597.x
|View full text |Cite
|
Sign up to set email alerts
|

The increased density of p38 mitogen-activated protein kinase-immunoreactive microglia in the sensorimotor cortex of aged TgCRND8 mice is associated predominantly with smaller dense-core amyloid plaques

Abstract: The role for phosphorylated p38 mitogen-activated protein kinase [p-p38(MAPK)] in β-amyloid plaque deposition [a hallmark of Alzheimer's disease (AD) pathology] remains ambiguous. We combined immunohistochemistry and stereological sampling to quantify the distribution of plaques and p-p38(MAPK)-immunoreactive (IR) cells in the sensorimotor cortex of 3-, 6- and 10-month-old TgCRND8 mice. The aggressive nature of the AD-related human amyloid-β protein precursor expressed in these mice was confirmed by the appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…Transection of the spinal cord or ablation of sensorimotor cortex reduced the formation of A␤ peptides in the affected regions further confirm the source of A␤ peptides. These results indicate that the sensorimotor cortex is highly susceptible to amyloid pathology [36]. This is consistent with a recent clinical study, which showed sensorimotor cortex is one of regions that is particularly vulnerable during the progression of AD in patients [37].…”
Section: Sensorimotor Cortex Was Highly Susceptible To Amyloid Pathologysupporting
confidence: 92%
“…Transection of the spinal cord or ablation of sensorimotor cortex reduced the formation of A␤ peptides in the affected regions further confirm the source of A␤ peptides. These results indicate that the sensorimotor cortex is highly susceptible to amyloid pathology [36]. This is consistent with a recent clinical study, which showed sensorimotor cortex is one of regions that is particularly vulnerable during the progression of AD in patients [37].…”
Section: Sensorimotor Cortex Was Highly Susceptible To Amyloid Pathologysupporting
confidence: 92%
“…In some tissues, like bone marrow monocytes, an increase in the levels of p38 MAPK activation is associated with aging444555. In this study, we found that p38 MAPKs are highly activated in monocytes of older mice compared to young mice, suggesting that p38α may display a stronger effect on osteoclastogenesis in old mice than in young mice and as such, p38 ablation may show more robust effects on monocyte proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 51%
“…S6), we suspect that the difference might be attributable to environmental changes in older mice. An increase in p38 MAPK activation in older mice has been reported in a few other tissues, which may reflect the accumulation of stress4445. Enhanced p38 MAPK activation may restrict monocyte proliferation in older mice to a greater extent than that in young mice; p38α deficiency may relieve this restriction and lead to greater expansion of monocytes in older mice than in young mice.…”
Section: Resultsmentioning
confidence: 85%
“…, 2009) 1:250; 53BP1 #305 (Nelson et al. , 2009) 1:1000 (Novus Biochemicals, Cambridge, UK); phosphor‐p38 #4631 (Chlan‐Fourney et al. , 2011) 1:50; 4‐HNE #HNEJ‐2 (Imai et al.…”
Section: Methodsmentioning
confidence: 99%